Analisis Kepentingan Tiongkok Untuk Compliance Terhadap Paris Agreement UNFCCC 2015-2020 - Firstyarinda Valentina Indraswari; Fariza, Ira Rahma (Department of International Relations, Brawijaya University, 2022)
World problems related to climate change are in the spotlight of new discussions that are being hotly discussed again by countries. The formation and negotiation of the Paris Agreement is one of the real implementations that proves the seriousness of the international community in viewing the increasing temperature of the earth due to extreme climate change. China as the country with the largest greenhouse gas emission contributor in the world is a key actor in the success of the targets in the Paris Agreement. In the midst of its big ambitions to become the world's largest economy and industrial country, China is required to remain fully committed to the Paris Agreement program to contribute to the successful reduction of world greenhouse gas emissions by 2030. Maintain compliance with the Paris Agreement program in the midst of the dilemma of high domestic economic interests. This paper will be analyzed using explanative qualitative research methods and is equipped with Compliance Theory from Ronald B. Mitchell as an analytical tool. With the results of China's self-interest factor in the success of its compliance with the Paris Agreement as seen from the outputs, outcomes, and impact variables.Keywords: China, Paris Agreement, Gas Emissions, Interest, Compliance